2016
DOI: 10.1097/sap.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Videoconference With Smartphones in Telemedicine Facial Trauma Care

Abstract: The proposed model to facial assessment trauma by videoconference via smartphones is feasible, showing high concordance level with face-to-face assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…Using this platform, forty-four percent of transfer requests were avoided [10] . Similar results report on telemedicine consultation for patients with facial, hand, ophthalmic, and burn injuries [11] , [12] , [13] , [14] . We think taken together, a structured plan is feasible and potentially helpful in managing those with mild-TBI and avoiding low value transfer.…”
Section: Discussionsupporting
confidence: 84%
“…Using this platform, forty-four percent of transfer requests were avoided [10] . Similar results report on telemedicine consultation for patients with facial, hand, ophthalmic, and burn injuries [11] , [12] , [13] , [14] . We think taken together, a structured plan is feasible and potentially helpful in managing those with mild-TBI and avoiding low value transfer.…”
Section: Discussionsupporting
confidence: 84%
“…Fonseca et al reported high concordance between in-person evaluations of facial trauma patients and evaluations carried out through smartphone videoconferencing with review of CT imaging. 62 A remote approach for triage can avoid unnecessary transfers for patients that do not require urgent intervention, and possibly reduce length of hospitalization.…”
Section: Facial Plastic and Reconstructive Surgerymentioning
confidence: 99%
“…A prospective study by Fonseca et al 26 compared the independent evaluation of patients with traumatic facial injuries in the ED by an in‐person surgery team vs a remote telemedicine team using videoconferencing by smartphone and tablet (n = 50). There was substantial concordance of physical exam findings ( κ = 0.720), and almost perfect concordance of facial CT scan findings ( κ = 0.899) and treatment recommendations ( κ = 0.891) as assessed by a standardized questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…There was substantial concordance of physical exam findings ( κ = 0.720), and almost perfect concordance of facial CT scan findings ( κ = 0.899) and treatment recommendations ( κ = 0.891) as assessed by a standardized questionnaire. Telemedicine was shown to be feasible and accurate in the evaluation of facial trauma, with the potential to optimize triage, length of stay, transfers, and patient cost in part by extending the possible area covered by a single surgeon compared to face‐to‐face evaluations 26 …”
Section: Resultsmentioning
confidence: 99%